Effect of flow rate and CNM concentration in nanofluid on the performance of convective heat transfer coefficient - Anggono, Agus Dwi; Riswanto, Danur; Ismoen, Muhaimin; Masyrukan,; Hariyanto, Agus; Sedyono, Joko (Frontiers in Mechanical Engineering, 2023)
The aim of this study is to investigate the thermal performance of water-based Carbon Nano Material (CNM) nanofluids, particularly in the convective heat transfer coefficient (h) parameter, and to analyze the effects of nanoparticle concentration and flow rate on an experimental heat transfer system. To achieve this, the researchers prepared the nanofluid through a 2-step method. In the first step, we mixed the nanoparticles with the base fluid using a magnetic stirrer to ensure homogenization, with the CNM-Water ratio set at 30, 75, 120, and 150 ppm. In the second step, we characterized the prepared samples, determining their size, composition, and particle morphology through PSA and SEM-EDX examination, as well as measuring their density (ρ) and specific heat (Cp). The experiments were carried out using a flow rate simulation test rig with a data acquisition system, at different flow rates of 0.2, 0.6, 1, and 1.4 L/min. Temperature (T) was measured at the inlet, outlet, and heater to determine the convective heat transfer coefficient value. The study successfully investigated the direct impact of CNM concentration and flow rate, with the results showing a consistent and expected value of the coefficient compared to previous studies. The highest coefficient value was observed at 150 ppm CNM-Water ratio and a flow rate of 1.4 L/min, with a value of 1825.37 W/(m2.K).